The Worst of Both Worlds: How U.S. and U.K. Models are Influencing Australian Education - Stephen Dinham (Arizona State University, 2015)
This commentary explores the so-called global 'crisis' in education and the corresponding pressures and moves to 'reform' education, and in particular, public education. The myths underpinning and driving these developments are examined. Supposed problems with (public) education and proposed solutions are explored. The solutions include government, institutional and corporate support for non-traditional forms of schooling such as government funded independent, for-profit schools, free schools, charter schools, cyber schools and academies. These are proliferating despite a lack of supporting evidence and in some cases in spite of non-supportive evidence. General deregulation of education at all levels and a belief in the power of market forces to improve teaching, schooling and student achievement drive these developments, in which Australia is following closely in the footsteps of models developed in U.S. and the UK. Cumulatively, these forces and developments are resulting in the discrediting and dismantling of public education. Rather than being addressed and rectified, disadvantage is being reinforced and inequity deepened, widened and entrenched, something that is ultimately bad for everyone in society.